2011
DOI: 10.1016/j.jvs.2010.06.154
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of robotic technology in vascular and endovascular surgery

Abstract: Robotic technology may enhance vascular surgical techniques given preclinical evidence and early clinical reports. Further clinical studies are required to quantify its advantages over conventional treatments and define its role in vascular and endovascular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(79 citation statements)
references
References 50 publications
0
77
1
1
Order By: Relevance
“…The available studies on rectal resection of the present review with a mean number of 14.3 harvested lymph nodes did not demonstrate inferior results in these terms. The oncologic outcome of robot-assisted rectal resection is an interesting Undoubtedly, the application of robotics in urology, gynecology, general, vascular, and cardiac surgery has provided increased operative dexterity and enhanced competence [66][67][68][69][70]. Whereas intracorporeal colocolic or colorectal anastomosis is a difficult task using conventional laparoscopic techniques, robotics offer a significant advantage in these terms.…”
Section: Discussionmentioning
confidence: 99%
“…The available studies on rectal resection of the present review with a mean number of 14.3 harvested lymph nodes did not demonstrate inferior results in these terms. The oncologic outcome of robot-assisted rectal resection is an interesting Undoubtedly, the application of robotics in urology, gynecology, general, vascular, and cardiac surgery has provided increased operative dexterity and enhanced competence [66][67][68][69][70]. Whereas intracorporeal colocolic or colorectal anastomosis is a difficult task using conventional laparoscopic techniques, robotics offer a significant advantage in these terms.…”
Section: Discussionmentioning
confidence: 99%
“…By these means, MSTUs may play a pivotal role in reducing the ischemic insult to the patient's brain, overall AIS morbidity and mortality, and societal cost for medical care, rehabilitation, and disability related to AIS. 3,16 After the idea for an MSTU was first proposed in Germany in 2003, the first MSTU became operational in Berlin in 2008. Data collected from early German MSTUs supported the feasibility of this mobile AIS treatment system and suggested MSTU deployment resulted in significantly decreased times to IV-tPA administration for the patient.…”
Section: Mobile Stroke Treatment Unitsmentioning
confidence: 99%
“…3,6,28,38,39 Lu et al reported their initial experience with robotically assisted diagnostic angiography in 15 patients using the Vascular Interventional Robot (VIR-2; Navy General Hospital of People's Liberation Army, Beijing University, China). The authors reported a mean (± SD) robotically assisted diagnostic angiography time of 34.4 ± 5.13 minutes and reported no periprocedural complications.…”
Section: Roboticsmentioning
confidence: 99%
“…RVIS (Robot-assisted VIS) has many advantages compared to conventional VIS [3][4][5][6][7]. First, surgeons could control the robot outside of the operating room by remote operation, which can avoid X-ray irradiation.…”
Section: Tsai@buaaeducnmentioning
confidence: 99%